Enantiospecific formal synthesis of inthomycin C - Athawale, Paresh R.; Kashinath, K.; Reddy, D. Srinivasa (Chemistry Select, 2016)
An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)-inthomycin C and (3S)-inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural product inthomycin C.

Efforts to access the potent antitrypanosomal marine natural product janadolide: synthesis of des- tert -butyl janadolide and its biological evaluation - Athawale, Paresh R.; Jachak, Gorakh; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, Srinivasa (ACS Omega, 2018)
To identify novel antitrypanosomal agents based on Janadolide, a potent macrocyclic polyketide–peptide hybrid, a macrolactonization strategy was explored. We prepared des-tert-butyl Janadolide and evaluated its antitrypanosomal activity. Our findings suggest that the tert-butyl group is necessary for the desired bioactivity.